Kingdom of the Netherlands-Netherlands : Financial Sector Assessment Program:: Technical Note-Regulation,Supervision, and Oversight of Financial Market Infrastructures-Responsibilities and EUROCCP Financial and Operational Risk Management. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the findings and recommendations in the Financial Sector Assessment Program for the Netherlands on regulation, supervision, and oversight of financial market infrastructures (FMIs), whose supervision has been significantly strengthened in recent years. Good progress has been made to ensure that FMIs across the European Union, including in the Netherlands, are subject to a common regulatory framework. It is suggested that the Dutch central bank review the allocation of resources across various FMIs. The European Central Counterparty N.V. should also prioritize recruitment of a third Management Board member to ensure an effective board.